KORELASI ANTARA KECERDASAN EMOSIONAL ANAK DENGAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA KELAS VIII SMP NEGERI 2 SAMPANG - Ali Nurhadi, (Pelangi Ilmu, 2010)
Abstract The emotional achievement is one of the dimensions that needs attention in order to develop the education because, recently, the result of the research shows the emotional intelligence (EQ) influence more on someones success if it is compared to intellectual intelligence (IQ). Meanwhile, one of the students succeeded indicators is getting the high achievement. In the other hand, the effort to develop the civic education (PKn) needs to be done because the students attention to the civic education also becomes less. For that matter, this research is used as an effort to prove the relation between the emotional intelligence and the learning achievement, especially on the civic education. In this research, there are two variables, they are independent variable (X), that is the students emotional intelligence, and dependence variable (Y), that is the learning achievement of civic education. The type of this research is descriptive quantitative analysis with correlational study. The population of this research is the students grade VIII State Junior High School 2 Sampang. Meanwhile, the sample of this research is 60 students and it is gotten by proportional random sampling technique using lottery. The method in collecting data is used by enquette and documentation. The data analysis is using product moment correlation statistic. The result of this research shows that there is correlation between the students emotional intelligence and the civic education learning achievement. It is proved from the counting result of calculation r = 0, 696 is bigger than the table r with N=60 in 1% = 0,330 significance standard, meanwhile in 5%=0,254.